The Influence of Accounting Information Systems and HR Competence on the Performance of MSMEs Mediated by E-Commerce - Jufri, Ali; Hadiwibowo, Imam; Safitri, Nabila; Dewi, Vinda Auralia Kesuma (Jurnal Riset Akuntansi dan Keuangan, 2024)
This research aims to determine the influence of accounting information systems and human resource competence on the performance of MSMEs mediated by e-commerce in Cirebon City. The research method used is descriptive with a quantitative approach. The sampling technique used was 110 business units and  Eviews 12 for data processing. The research results found that e-commerce and financial literacy did not partially influence the performance of MSMEs, while accounting information systems and accounting knowledge partially influenced the performance of MSMEs. However, simultaneously e-commerce, accounting information systems, accounting knowledge and financial literacy influence the performance of MSMEs. This research makes a contribution by examining the influence of E-Commerce, accounting information systems, accounting knowledge, and financial literacy on the performance of MSMEs in Cirebon City. This research offers an in-depth understanding of the role of e-commerce, accounting information systems, accounting knowledge, and financial literacy on the performance of MSMEs in Cirebon City.